Cyclophosphamide Versus Mycophenolate Versus Rituximab in Lupus Nephritis Remission Induction: A Historical Head-to-Head Comparative Study. Issue 1 (January 2019) - Goswami, Rudra Prosad; Sircar, Geetabali; Sit, Hiramanik; Ghosh, Alakendu; Ghosh, Parasar
Abstract : Objective: We report comparative efficacy between high-dose cyclophosphamide (HDCyC), low-dose cyclophosphamide (LDCyC), mycophenolate mofetil (MMF) and rituximab in patients with lupus nephritis (LN). Methods: We analyzed comparative efficacy of 4 induction regimens of biopsy-proven LN: LDCyC: 500 mg fortnightly, HDCyC: 750 to 1200 mg monthly, MMF: 1.5 to 3 g/d, and rituximab. Outcomes of 4 groups were analyzed at the sixth month. Results: Among a total 222 patients, 26 received LDCyC (3-g total dose), 113 received HDCyC (mean, 5.1-g total dose), 61 received MMF (mean, 2.2 g/d), and 22 received rituximab (mean, 1.9-g total dose). Relapsing/refractory LN was 11 in HDCyC, 1 in LDCyC, 10 in MMF, and 14 in the rituximab group. Overall 16.2% had no improvement of proteinuria, 18% had partial response, and 65.8% (146/222) had complete response. Renal response (RR) was higher in HDCyC (90.3%) and rituximab (90.9%) groups compared with LDCyC (73%) and MMF (72%) groups. Rituximab was effective in relapsing disease (100% RR). Infection was highest with the HDCyC, followed by LDCyC and rituximab ( p = 0.15), whereas the MMF group had a higher incidence of gastrointestinal adverse effects ( p < 0.001). The following predictors of RR were identified: rituximab (odds ratio [OR], 20.4; 95% confidence interval [CI], 1.9–215.7; p = 0.012), renal Baseline Systemic Lupus Erythematosus Disease Activity Index at baseline (OR, 0.86; 95% CI, 0.75–0.99; p = 0.034), and duration of disease (OR, 0.98; 95% CI, 0.97–0.99; p = 0.009). Conclusions: High-dose cyclophosphamide and rituximab were the most effective therapeutic strategies in patients with LN, especially in the Indian context. Rituximab was highly effective in relapsing disease.